2020
DOI: 10.3897/zookeys.939.50612
|View full text |Cite
|
Sign up to set email alerts
|

Immature stages of Palearctic Mecinus species (Coleoptera, Curculionidae, Curculioninae): morphological characters diagnostic at genus and species levels

Abstract: The immature stages of ten Mecinus species are described for the first time and those of two other species are redescribed, adding important chaetotaxy characters that were missing from previous descriptions. These species belong to six of the nine assemblages of Mecinus species previously established according to a phylogenetic analysis. All these groupings are confirmed on the basis of several characters of mature larvae and pupae. Moreover, all the species show several characters that are useful for disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The complex of these new data have allowed us to support that (1) Lachnaeus and Rhinocyllus are two valid genera that are different from Larinus , (2) Rhinocyllini is not a tribe different from Lixini, and (3) the separation of Rhinocyllus into two subgenera is rational. Therefore, it seems obvious why it will be important to increase the exiguous number of species of this tribe with known immature stages in order to address other unresolved questions, as already shown in other tribes or subfamilies (see Otiorhynchinini [ 43 ], Cionini [ 44 ], Mecinini [ 45 , 46 ], Smicronychini [ 47 ], Tychiini [ 42 ] and Cossoninae [ 48 ]). It is clearly confirmed that a detailed description of immature stages is a very important component for a better understanding of generic taxonomy but also tribal taxonomic and phylogenetic relationships within Lixinae, as well as within other subfamilies (see above).…”
Section: Discussionmentioning
confidence: 99%
“…The complex of these new data have allowed us to support that (1) Lachnaeus and Rhinocyllus are two valid genera that are different from Larinus , (2) Rhinocyllini is not a tribe different from Lixini, and (3) the separation of Rhinocyllus into two subgenera is rational. Therefore, it seems obvious why it will be important to increase the exiguous number of species of this tribe with known immature stages in order to address other unresolved questions, as already shown in other tribes or subfamilies (see Otiorhynchinini [ 43 ], Cionini [ 44 ], Mecinini [ 45 , 46 ], Smicronychini [ 47 ], Tychiini [ 42 ] and Cossoninae [ 48 ]). It is clearly confirmed that a detailed description of immature stages is a very important component for a better understanding of generic taxonomy but also tribal taxonomic and phylogenetic relationships within Lixinae, as well as within other subfamilies (see above).…”
Section: Discussionmentioning
confidence: 99%
“…The number of larval instars in weevils is correlated primarily with the body size of a species. Thus, small species (head width of the mature larva below ~ 0.65 mm) usually have only three larval instars (Dosdall et al 2007;Gosik et al 2020;Skuhrovec et al 2022), whereas larger species can have up to seven instars (Skuhrovec et al 2022).…”
Section: Larval Instar Determination and Growth Factor Calculationmentioning
confidence: 99%